The Resilience of Traditional Trade Union Practices in the Revitalisation of the Argentine Labour Movement - Atzeni, Maurizio (2007)
Fil: Ghigliani, Pablo. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Instituto de Investigaciones en Humanidades y Ciencias Sociales (UNLP-CONICET); Argentina.